UXUC - User experience & urban creativity scientific journal, vol.2, nº1 (Dez. 2020) - Neves, Pedro Soares (2021)
The issue opens with Philipp Shadner’s discussion of the 1970s punk movement, which not only questioned and provoked aesthetic values but also has had a major influence on the multitude of styles of urban art until the present. Shadner gives us insights into the history of the punk movement, the symbols and slogans punks used and still use not only for tagging urban spaces, but also put temporarily or permanently on their skins and/or their clothes to create a visual struggle against the conformist mainstream society. Arthur Crucq’s article analyses the social and political role of collaboratory art in an urban community in The Hague, Netherlands. Using examples of textile installations, Crucq’s discussion centers on recognizing community art projects as autonomous platforms for the development of political agency in the urban space. Jeni Peake looks at street art activism from the perspective of linguistics. Peake explores English graffiti found in urban spaces in the city of Bordeaux, France. With a large number of the graffiti examples adhering to many themes of social struggle, Peake’s article seeks to establish to what extent the use of English could be understood as a political or at least rebellious and creative act. Angelos Evangelidis examines the political posters on the walls of the streets in Athens that worked as both a visual and political platform for the anti-austerity movement in Greece (2010-2015). Furthermore, Evangelinidis’ literature review shows that the dialectical relationship between urban space and visual practice is the key to map the process of art’s role in social struggles.